(untitled) (Лучшие интеллектуальные исследования, 2025)
The language of philosophy is a tapestry woven with intricate conceptual threads, each carrying the weight of historical, cultural, and intellectual traditions. As philosophical ideas evolve over time, the very words used to convey these abstract notions undergo semantic transformations, reflecting the shifting sands of intellectual discourse. This review article explores the diachronic shifts in the semantics of philosophical terminology in both Uzbek and English, shedding light on the complex interplay between linguistic representation and the development of philosophical thought.